Determinants of students’ approach to learning biology at the university level - Olić Ninković, Stanislava; Adamov, Jasna (Biologia Serbica, 2023)
This research examined students' approaches to learning biology and tested differences in learning approaches between students of different study programs, different genders and years of study. The sample included 141 students (120 female and 21 male) from the Department of Biology and Ecology of the Faculty of Science, University of Novi Sad (Serbia). The results showed that about half of the examined students have a deep approach to learning, followed by a surface and a strategic one. The differences in approaches to learning in relation to the study program, gender and year of study did not prove to be significant.